HUBUNGAN PENGETAHUAN LINGKUNGAN DENGAN PERILAKU SISWA DALAM MENJAGA KEBERSIHAN LINGKUNGAN - Resyi A Gani (Jurnal Elementary:Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2022)
The purpose of this study was to determine the relationship between students' environmental knowledge and student behavior in maintaining environmental cleanliness. This research is a quantitative study with a correlation approach on environmental knowledge as the independent variable and student behavior in maintaining environmental cleanliness as the dependent variable. The subjects of this study were classes IVB, VB, and VIA SD Negeri Citaringgul 01, Babakan Madang District, Bogor Regency, in the 2020/2021 academic year totaling 114 with a sample of 88 respondents. The research data was obtained by using multiple choice test questions for students' environmental knowledge variables and a questionnaire questionnaire for students' behavior variables in maintaining environmental cleanliness. The results showed that there was a positive and significant relationship between students' environmental knowledge and student behavior in maintaining environmental cleanliness. This is based on statistical analysis which produces a path coefficient (rxy) of 0.334 and in the pattern = 69.36 + 0.49x, while the determinant coefficient is 11.2% and the remaining 88.8% is determined by other factors. Based on the results of these studies, it can be concluded that there is a low relationship between students' environmental knowledge and student behavior in maintaining environmental cleanliness.